The disturbing order and Hafez's ghazals - Naser Rahimi; Zoheir Nadalizadeh (مطالعات زبانی و بلاغی)
The incoherent structure and disturbed formulas of some lines in Hafez's ghazals have been studied for a long time. Scholars` research on Hafez have made much endeavor, to either justify the aforesaid structure or rather offer the possible rationale behind this lack of coherence. By reviewing them even briefly, one can lend more credibility and value to some proposed hypotheses and theories in that respect, and conveniently put the rest aside. In this paper, while examining the question, I investigated thorough a selected body of the major existing hypotheses which have set themselves the task of explaining this peculiar structure in Hafez's ghazals. Then, I proposed new insights for its understanding which aimed to justify the incoherence of the lines and the diversity of the topics of his ghazals from a musical perspective. To that intent, I formulated my hypothesis based upon the poetic texture and the intertextual relations of Hafez's poems as a whole.